المضاعفات الشريانية للقثطرة الشريانية مع التشخيص والتدبير - علي سليمان (Latakia University Journal -Medical Sciences Series, 2019)
كثر في الآونة الأخيرة إجراء القثطرة الشريانية كوسيلة تشخيصية وعلاجية للعديد من الأمراض القلبية والوعائية، وبسبب ذلك ارتفعت نسبة المضاعفات الناجمة عنها والتي تسببت بدرجات مختلفة من الامراضية. ولقد قمنا في هذا البحث بدراسة هذه المضاعفات وأسباب حدوثها بالإضافة إلى طرق تشخيصها وتدبيرها حسب نوعها والمدخل الشرياني المستخدم. كما أجرينا مقارنة بين دراستنا المجراة على 1500 حالة انتقائية وعدة دراسات عالمية في هذا المجال. هذا البحث يؤكد على أن الإجراءات الوقائية تمنع الكثير من المضاعفات التي يجب تشخيصها وتدبيرها بأسرع ما يمكن في حال حدوثها. Cutter Recently, arterial catheterization has been performed as a diagnostic and therapeutic method for many cardiovascular or vascular diseases, and because of this, the percentage of complications caused by it has increased. In this study, we have studied these complications and their causes of their occurrence in addition to the methods of diagnosis and management by type and the portal arterial user. We have compared our study with 1500 selective cases and several international studies in this field. This research confirms that preventive measures prevent many complications that must be diagnosed and managed as soon as possible in case they occur.